MPEG1/Perforin-2 Haploinsufficiency Associated Polymicrobial Skin Infections and Considerations for Interferon-γ Therapy - Merselis, Leidy C.; Jiang, Shirley Y.; Nelson, Stanley F.; Lee, Hane; Prabaker, Kavitha K.; Baker, Jennifer L.; Munson, George P.; Butte, Manish J. (Frontiers in Immunology, 2020)
Introduction: Macrophage expressed gene 1 (MPEG1) is highly expressed in macrophages and other phagocytes. The gene encodes a bactericidal pore-forming protein, dubbed Perforin-2. Structural-, animal- and cell-based studies have established that Perforin-2 facilitates the destruction of phagocytosed microbes upon its activation within acidic phagosomes. Relative to wild-type controls, Mpeg1 knockout mice suffer significantly higher mortality rates when challenged with gram-negative or -positive pathogens. Only four variants of MPEG1 have been functionally characterized, each in association with pulmonary infections. Here we report a new MPEG1 nonsense variant in a patient with the a newly described association with persistent polymicrobial infections of the skin and soft tissue. Case Description: A young adult female patient was evaluated for recurrent abscesses and cellulitis of the breast and demonstrated a heterozygous, rare variant in MPEG1 p.Tyr430*. Multiple courses of broad-spectrum antimicrobials and surgical incision and drainage failed to resolve the infection. Functional studies revealed that the truncation variant resulted in significantly reduced capacity of the patient’s phagocytes to kill intracellular bacteria. Patient-derived macrophages responded to interferon gamma (IFN-) by significantly increasing the expression of MPEG1. IFN- treatment supported Perforin-2 dependent bactericidal activity and wound healing. Conclusions: This case expands the phenotype of MPEG1 deficiency to include severe skin and soft tissue infection. We showed that haploinsufficiency of perforin-2 reduced the bactericidal capacity of human phagocytes. Interferon-gamma therapy increases expression of perforin-2, which may compensate for such variants. Thus, treatment with IFN- could help prevent infections.